APPLICATION OF FINANCIAL MANAGEMENT PROJECT PT. JAYA USING VISUAL BASIC 2008 KENCANA AND MS. ACCESS - Sisca Amalia Oktaviani; Irfan ,S. Kom, MMSI (Jurnal Sistem Informasi, 2008)
Along with population growth and development The rapid town, the development ofinfrastructure necessary and urban infrastructure to improve the quality of life communitiesand supporting various community activities and the government is in it. One aspect ofconstruction-related fields such business is Contracting (contracting services), particularly inparts Mechanical Electrical and Elevator Escalator, where PT. Victorious Kencana hasdiligently handled since 1965. Now, PT. Jaya Kencana has been recognized as one of thecontractors Indonesia's leading because the reliability and accuracy the basis of service timeto customers. PT. JAYA KENCANA manage so many projects in Indonesia especially inJakarta on a large scale or small, this illustrates that. JAYA KENCANA requires a system toprioritize the ease and speed of operation is the course of an administrative order to supporttechnical work.APPLICATION OF FINANCIAL MANAGEMENT PROJECT PT. JAYA USING VISUALBASIC 2008 KENCANA AND MS. ACCESS is expected to become an application that canaccommodate and access all the data needs finance the entire project, can facilitate practicalfinancial monitoring of project budgets, where it can be a reference project manager indecision making cash disbursements.